THE USE OF LOCAL LEGUMES IN THE DIET THERAPY OF CHRONIC HEPATITIS - Zokirkhodjayev, S.Y.; Jalolov, N.N.; Ibragimova, M.M.; Makhmudova, I.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
the possibility of using in soups of chronic hepatitis soups from local bean products prepared using the new technology, and evaluating their effectiveness. Material and methods: studies were conducted on 47 patients with chronic hepatitis who were treated in the 2nd therapeutic department of the 1st TMA clinic. They were divided into 2 groups: the 1st one - the usual diet therapy, the 2nd one - with the Parhez Mohor diet therapy prepared from local beans. Results: In the period of exacerbation of chronic hepatitis, the clinical picture, laboratory and instrumental parameters change according to the severity of the disease. The use of the “Parhez Mohora” dish, prepared on the basis of the new technology, as a dietary therapy, had a positive effect on the dynamics of the disease, manifested by a significant improvement in the enzyme spectrum of the blood serum and normalization of hematological parameters. This is due to specific vegetable proteins, the content of polyunsaturated fatty acids, carbohydrates in the form of starch, mono- and disaccharides, as well as a high content of vitamins of group B, E, C, PP.